Cyber Politics and Cyber Law: Online Hate Speech and Political Misinformation in Pakistan - Muhammad Huzaifa Bin Salih; Ammara Afzal Siddiqui; Ayisha Safdar; Syeda Asma Hussain; Fatima Ilyas; Zahir Mehmood (`, 2025)
The digital revolution has brought a new dimension to the world of political communication, and has provided an opportunity to participate, mobilize and discuss. Online communities Facebook, X (previously, Twitter), and Tik Tok have become an important platform for political action in Pakistan especially among young people. But online hate speech, trolling, and political misinformation, which have spread dramatically over the same platforms, have become important sources of threat to social cohesion, democratic institutions, and freedom of expression. The current paper explores the overlap between the idea of cyber politics and the notion of cyber law in Pakistan and the Prevention of Electronic Crimes Act (PECA) 2016. Using a qualitative data study, case study, and a doctrinal legal research method, the research examines how hate speech and misinformation on the Internet are regulated and the problem of selective enforcement, as well as the overarching issue of democracy. The findings show that PECA presents a legal tool in responding to the harms of online offenses but due to its ambiguous nature, and an inadequate alignment between its application and enforcement, its application is ineffective and invalid. Digital spaces are widely exploited by actors in politics, and simultaneously regulation is invoked politicising cyber governance even more. The relative international perspectives illustrate Pakistan as alternating between laxity and over-censorship, in contrast to hybrid combinations of co-regulation in other countries. Since the evidence presented in the paper indicates that Pakistan needs a balanced and rights-driven strategy to improve accountability, facilitate digital literacy, and secure freedom of expression and prevent harmful online behavior. Keywords: Cyber politics, Cyber law, PECA 2016, Hate speech, Misinformation, Disinformation, Social media, Political communication, Freedom of expression, Pakistan